A Tale of Two Cities - "Dickens, Charlies"; English-Fiction (Puffin Books: India, 2009)
Charles Darnay and Sydney Carton may look the same but their personalities are very different. When Charles returns to Paris to attempt to save his servant, having fled to London from the French Revolution, he endangers his own life. Sydney may be able to help with his strong resemblance, and hopefully can also save Charles' life
Keywords: English-Historical fiction